The immunoreactivity of a chimeric multi-epitope DNA vaccine against IBV in chickens - Tian, Lang (Biochem Biophys Res Commun, 2008)
Epitope-based vaccines designed to induce cellular immune response and antibody responses specific for infectious bronchitis virus (IBV) are being developed as a means for increasing vaccine potency. In this study, we selected seven epitopes from the spike (S1), spike (S2), and nucleocapsid (N) protein and constructed a multi-epitope DNA vaccine. The 7-day-old chickens were immunized intramuscularly with multi-epitope DNA vaccine encapsulated by liposome and boosted two weeks later, and were challenged by virulent IBV strain five weeks post booster. The results showed that multi-epitope DNA vaccine led to a dramatic augmentation of humoral and cellular responses, and provided up to 80.0% rate of immune protection. The novel immunogenic chimeric multi-epitope DNA vaccine revealed in this study provided a new candidate target for IBV vaccine development.